INFLUENCE OF ACICULAS DEPOSITION ON NATURAL REGENERATION IN SUB-WOODS OF Pinus taeda L. FOREST STAND - Fockink, Guilherme Diego; Pech, Tatiani Maria; Silva, Mayrine; Siminski, Alexandre; Niemeyer, Júlia Carina (Floresta, 2019)
This study was conducted in a commercial forest stand of Pinus taeda L. located in Curitibanos, in the State of Santa Catarina, Brazil. The objective of this study was to evaluate the influence of the physical barrier caused by the deposition of aciculas, on natural regeneration mechanisms of native species in sub-woods of P. taeda L. forest stand. Three plots (10 x 10 m) were installed in the sub-woods of the forest stand, and the natural regeneration was evaluated in the control (presence of aciculas) and clean (absence of aciculas) subplots, in addition to the seeds rain and soil seeds bank. The density and frequency parameters (absolute and relative) and the Shannon-Weaver Index (H’) were calculated, and the total density values of the seeds rain and seeds bank were subjected to ANOVA (p<0.05), while the density of regenerative seedlings was subjected to Student’s t Test (p<0.05), using the Software R Studio ®. The density of regenerative seedlings (ind.m-2) was higher in clean subplots, statistically. No significant statistical difference was observed for the density parameter (ind.m-2) among the subplots for the soil seeds bank, but only for the seeds rain. Shannon Diversity Index was higher in the plots closer to the fragment in all evaluated mechanisms. The obtained results indicate that the litter layer acts as a physical barrier to the breeding of the seeds bank and prevents the arrival of the seeds rain propagules directly to the soil, hindering the establishment of native plants and, consequently, the natural regeneration in the sub-woods.